PENGARUH PARTISIPASI PENGANGGARAN, KEADILAN PROSEDURAL, DAN GAYA KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI - Nur Dian Fitriana; Soliyah Wulandari; Yahya Hamzah (Department of Accounting-Faculty of Economic and Business (FEB), 2014)
This study describes the influence of budgetary partisipation, procedural justice,and leadership style on organizational commitment. Sample of this research obtained fromemployee in hospitals and clinics in South of Tangerang. Final samples are 109 respondents.Respondents in this study were employees , because they can assess the variables of budgetparticipation, procedural fairness , and with good leadership style based on experiencesduring their daily work. This study is limited to employees who work in hospitals andclinics in the region of South Tangerang. Methods of sample selection is done by simplerandom sampling. Data analysis was perfomed using multiple regressions. Results ofthis research provide empirical support for budgetary participation, proceduraljustice, and leadership style on organizational commitment. Partisipasi penganggaran,Keadilan procedural, dan Gaya kepemimpinan memiliki pengaruh terhadap komitmen organisasi.DOI: 10.15408/akt.v7i1.2643